2020
DOI: 10.1002/mrm.28160
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance fingerprinting for simultaneous renal T1 and T2* mapping in a single breath‐hold

Abstract: Purpose To evaluate the use of magnetic resonance fingerprinting (MRF) for simultaneous quantification of T1 and T2∗ in a single breath‐hold in the kidneys. Methods The proposed kidney MRF sequence was based on MRF echo‐planar imaging. Thirty‐five measurements per slice and overall 4 slices were measured in 15.4 seconds. Group matching was performed for in‐line quantification of T1 and T2∗. Images were acquired in a phantom and 8 healthy volunteers in coronal orientation. To evaluate our approach, region of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…Recently, Marchenko–Pastur principal component analysis (MPPCA) was proposed to denoise EPI diffusion MRI images 14 . This is of particular interest, as a recent study demonstrated the value of denoising the acquired MRF magnitude images to improve the quality of the quantitative maps 10 . The large number of magnitude images in an MRF acquisition leads to long reconstruction times, which has been acknowledged as one of the drawbacks of the MRF methodology 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Marchenko–Pastur principal component analysis (MPPCA) was proposed to denoise EPI diffusion MRI images 14 . This is of particular interest, as a recent study demonstrated the value of denoising the acquired MRF magnitude images to improve the quality of the quantitative maps 10 . The large number of magnitude images in an MRF acquisition leads to long reconstruction times, which has been acknowledged as one of the drawbacks of the MRF methodology 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…First, T2 estimation was added to the previously introduced EPI-based MRF, making it possible to estimate all three main relaxation parameters in a single scan (T1, T2, and T2*). As also noted in previous work (Hermann et al, 2020;Rieger et al, 2018Rieger et al, , 2017, EPI-based acquisitions make use of online instantaneous image reconstruction and produce images without noticeable under-sampling artifacts. Second, the utilization of simultaneous multi-slice (SMS) acceleration combined with slice interleaving makes this method capable of acquiring each slice in a few seconds, consequently enabling whole-brain coverage in just a few minutes (3 minutes here with SMS factor of 4).…”
Section: Discussionmentioning
confidence: 61%
“…As the measured signals resemble the simulated ones, we were able to simplify the training process by not needing to acquire a large sample of undersampled data for realism of training. Furthermore, as motion correction has been recently raised as a means to improve MRF accuracy, the absence of undersampling artifacts in EPI images facilitates image-domain motion correction (Hermann et al, 2020). The high image quality also lends itself to possibly more accurate partial volume estimation through solving the inverse problem (Deshmane et al, 2019; Fang et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations